THE URGENCY OF EARLY CHILDHOOD CHARACTER EDUCATION (USING THE ROLE PLAY LEARNING METHOD) BASED ON THE QUR'AN AND HADITH IN THE PRESENT AND FUTURE TIMES - Sumarsilah, Sumarsilah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Character education aims to continuously improve the individual's self and train their abilities in order to lead a better life. The demand for education to produce quality students today and in the future will be an awareness that must continue to be echoed. The aim of this research is to provide understanding in early childhood character education using the Role Play learning method. This research uses qualitative research with Mary W. George's (2008) theory, namely a library research method. The data in this research is secondary data that is relevant to the topic, namely character education, role play learning methods, as well as the Al-Qur'an and hadith. The research method uses literature research or library research which will be discussed and concluded.